2022
DOI: 10.1002/cam4.4668
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of prognostic nutritional index in advanced cancer receiving PD‐1/L1 inhibitors: A meta‐analysis

Abstract: Purpose To study the prognostic value of the prognostic nutritional index (PNI) in advanced cancers receiving programmed death‐1/programmed death‐ligand 1 (PD‐1/L1) inhibitors. Methods Online electronic databases were comprehensively searched and available literature was retrieved. We extracted available data from included researches and pooled the hazard ratios (HRs) and 95% confidence intervals (CIs) to learn the prognostic value of PNI on overall survival (OS) or progression‐free survival (PFS); and meanwhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
(106 reference statements)
1
5
0
Order By: Relevance
“…In a recent meta-analysis, a low PNI signi cantly predicted worse PFS and OS and adversely affected the ORR in patients with advanced cancers who received PD-1 blockade treatment [21]. In these patients, the PNI was an excellent predictor when compared with other indices.…”
Section: Discussionmentioning
confidence: 96%
“…In a recent meta-analysis, a low PNI signi cantly predicted worse PFS and OS and adversely affected the ORR in patients with advanced cancers who received PD-1 blockade treatment [21]. In these patients, the PNI was an excellent predictor when compared with other indices.…”
Section: Discussionmentioning
confidence: 96%
“…In a recent meta-analysis, a low PNI significantly predicted worse PFS and OS and adversely affected the ORR in patients with advanced cancers who received PD-1 blockade treatment [21]. In these patients, the PNI was an excellent predictor when compared with other indices.…”
Section: Discussionmentioning
confidence: 99%
“…[9,10,[25][26][27][28][58][59][60][61] Studies have also looked at the relationship between PNI and immunotherapy and have found PNI to be an independent factor in the prognosis of immunotherapy patients. [29,62] Compared to other indicators, PNI is more suitable for the prediction of survival in the elderly and in patients with malignancies because it considers nutritional status and immunological status. These 2 groups of patients often have poorer nutritional status due to chemotherapy or receipt of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Other studies examined use of the PNI to predict outcome in cancer patients receiving an ICI-based therapy and concluded that a high PNI predicted a better outcome. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation